2021
DOI: 10.1186/s13073-020-00813-7
|View full text |Cite
|
Sign up to set email alerts
|

The complexities of the diet-microbiome relationship: advances and perspectives

Abstract: Personalised dietary modulation of the gut microbiota may be key to disease management. Current investigations provide a broad understanding of the impact of diet on the composition and activity of the gut microbiota, yet detailed knowledge in applying diet as an actionable tool remains limited. Further to the relative novelty of the field, approaches are yet to be standardised and extremely heterogeneous research outcomes have ensued. This may be related to confounders associated with complexities in capturin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 134 publications
0
50
0
Order By: Relevance
“…Secondly, we did not include in this study the metagenome analysis to explore gut microbiota dysbiosis in subjects with different chronotypes closely. However, it is well known that the very changeable composition of the gut microbiota might potentially hinder the robustness and reproducibility of microbiota—disease associative studies [ 20 , 60 , 61 , 62 ]. In addition, circulating TMAO concentrations have recently been included among the reliable biomarkers for gut dysbiosis [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, we did not include in this study the metagenome analysis to explore gut microbiota dysbiosis in subjects with different chronotypes closely. However, it is well known that the very changeable composition of the gut microbiota might potentially hinder the robustness and reproducibility of microbiota—disease associative studies [ 20 , 60 , 61 , 62 ]. In addition, circulating TMAO concentrations have recently been included among the reliable biomarkers for gut dysbiosis [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the Mediterranean dietary pattern is also the most characterized factor that influences the gut microbiota [ 19 ]. The complexity of studying the gut microbiota is, however, characterized by a high intra-individual variability of the daily food consumption of each subject that might potentially hinder the robustness and reproducibility of microbiota—disease associative studies [ 20 ]. We previously reported that the lowest adherence to the Mediterranean diet (MD) was associated with the highest circulating TMAO concentrations [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…These preliminary results seem to suggest a complex relationship between diet and gut microbiota that dietary macronutrient intake itself cannot fully explain. The integration with other factors, such as eating behaviors and nutrient provenance, and a more detailed analysis of micronutrients and food additives might shed light on the complex crosstalk between microbial communities and diet ( Leeming et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Microbes are an integral part of these systems, playing crucial roles in the biology of other organisms and contributing to the regulation of the overall systems (Habtamu et al, 2017;Hauffe & Barelli, 2019;Ruth et al, 2008;Stuart et al, 2013). Gut microbiota is personified with different functions of hostmicrobe interactions such as ecology, diet or food selection, behaviour, host immune system and the overall health of the host (Bahrndorff et al, 2016;Leeming et al, 2021). However, as animals and humans have come to live in close proximity and there are cases of frequent encroachments into one other territory; microbial parasites are now viewed as potential zoonotic agents for human wellbeing Jones et al, 2008;Keatts et al, 2021).…”
Section: Introductionmentioning
confidence: 99%